Association between Obstructive Lung Disease and Cardiovascular Disease: Results from the Vermont Diabetes Information System - Maria E. Ramos-Nino; Charles D. MacLean; Benjamin Littenberg (MDPI AG, 2021)
The association between obstructive lung disease and cardiovascular disease (CVD) has been suggested previously, but few studies have looked at this association in a diabetic cohort, a population highly susceptible to both comorbidities. A total of 1003 subjects in community practice settings were interviewed at home at the time of enrolment into the Vermont Diabetes Information System, a clinical decision support program. Patients self-reported their personal and clinical characteristics, including any obstructive lung disease. Laboratory data were obtained directly from the clinical laboratory. We performed a cross-sectional analysis of the interviewed subjects to assess a possible association between obstructive lung disease and CVD. In a multivariate logistic regression model, obstructive lung disease was significantly associated with CVD, even after correcting for potential confounders, including gender, obesity, low income, cigarette smoking, alcohol problems, and high comorbidity (odds ratio = 1.96; 95% confidence interval 1.37-2.81; p < 0.01). All components of CVD, including coronary artery disease (CAD), congestive heart failure (CHF), peripheral vascular disease (PVD), and cerebrovascular accidents (CVA), were also significantly associated with obstructive lung disease. These data suggest an association between obstructive lung disease and CVD in patients with diabetes. Future studies are needed to identify the mechanism supporting this association